Power and resource allocation for MIMO based two-tier heterogeneous network using small cell clustering algorithm - Prabhu Chandran, K.; G. P, Ramesh (International Journal of Engineering and Technology, 2017)
Resource allocation problem in the two-tier heterogen eous MIMO network plays a vital role in avoidance of interference between the mobile users connected to the host directly and through the backhaul link. Two different frequency bandwidths are proposed to avoid the interference generated between the users placed in the interference region in the small cell. The mobile user frequency range is allotted for the link between small cell base station, macrocell base station and mobile user and millimeter frequency bandwidth is utilized between the small cell base station, small cell cluster heads and small cell users. The inter-small cell clustering helps the small cell base station node to select the number of antennas for communication and to send the request for allocation of bandwidth to eliminate the inter-cell congestion. The method was implemented in NS2 simulator, and the performance matrices were measured to analyze the efficiency and quality of service of the proposed topology.